2018
DOI: 10.1029/2018gl077994
|View full text |Cite
|
Sign up to set email alerts
|

Strong Dependence of Extreme Convective Precipitation Intensities on Gauge Network Density

Abstract: Extreme convective precipitation on subhourly scales is notoriously misrepresented in rain gauge‐based observations, but uncertainties are weakly quantified at the 1 to 30 km scale. We employ a unique observing network, the high‐density WegenerNet and surrounding operational rain gauge network in southeastern Austria, to sample convective precipitation extremes at these scales. By systematically constructing lower‐density networks, we explore how estimated maximum area precipitation depends on observing statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 63 publications
2
38
0
Order By: Relevance
“…Multiple studies have shown that short-lived bursts are responsible for much of the runoff and erosion that takes place on agricultural, dryland, and other soils. Early studies of the importance of intensity peaks embedded within longer rainfalls include the work of Seginer et al (1962) in Israel. In a study of runoff and soil loss using rainfall simulation, they adopted a 4.5 h design storm that included an intense central 30 min period preceded and followed by lower intensity rain.…”
Section: What Evidence Points To the Significance Of Short-lived Intementioning
confidence: 99%
“…Multiple studies have shown that short-lived bursts are responsible for much of the runoff and erosion that takes place on agricultural, dryland, and other soils. Early studies of the importance of intensity peaks embedded within longer rainfalls include the work of Seginer et al (1962) in Israel. In a study of runoff and soil loss using rainfall simulation, they adopted a 4.5 h design storm that included an intense central 30 min period preceded and followed by lower intensity rain.…”
Section: What Evidence Points To the Significance Of Short-lived Intementioning
confidence: 99%
“…However, this traditional evaluation of precipitation has limitations for evaluating convective precipitation since the typical dimension of convective storms is smaller than the distance between stations. This can lead to an underestimation of storm frequency and storm peak intensity [5]. An evaluation of the space-time dynamics of convective cells requires the finer spatial and temporal resolution of remote sensing techniques.…”
mentioning
confidence: 99%
“…In addition, it is becoming increasingly clear that indices based on daily data will miss or mask some of the most intense events that could lead to flash flooding. This is particularly the case for convective extremes at point scale, found to be underestimated substantially by operational networks in a regional experiment (Schroeer et al 2018). While we have a limited knowledge of the processes that cause sub-daily extreme precipitation and its inherent intermittency…”
Section: Types Of Indicesmentioning
confidence: 97%